Gallium Selective PVC Membrane Electrodes Based on Crown Ethers - Abdulla, N. I (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
+ Gallium  selective  e lectrodes   based  on  12-crown-4  (12C4)  and benzo-15-crown-5   (B15C5)  and  plasticizers   dioctyl  phenyl phosphonate   (DOPP),   dibutyl  phosphate  (DBP),  dibutyl  phthalate (DBPH)  in  PVC  matrix  membranes  are  constructed.  Specific properties  of  the electrodes  are  studied  including  calibration  curve, slope  detection limit, concentration  range, response time and life tiMe as well as the effect of pH on electrode response. Interference for Li1  ,Mg2+,     Zn2+,     Al 3 +,     Cr3+     on   electrode   respons.e   have   been   alsoinvestigated.  The  polymetic   liquid  membrane  electrode   based  on12C4 using DBPH plasticizer exhibits the best over all performances as  a  gallium  selective  electrod e  over  a  wide  concentration  range (l.O x l0-5 - 3.3x10-2 M) with Nemestian slope (20mV/decade). It has a relatively  fast response  time excellent  detection  limit (7x 1o-6M) and good  durability  (about  2  m onths).  The  electrode  revealed  a  good + selectivity  for Ga3 over a variety of other  metal  ions and could  be used in a pH range of 3.0-5.0. It was used as an indicator electrode in potentiometric titration of gallium ions.